Optically Active Perovskite CsPbBr3 Nanocrystals Helically Arranged on Inorganic Silica Nanohelices - Liu, Peizhao; Chen, Wei; Okazaki, Yutaka; Battie, Yann; Brocard, Lysiane; Decossas, Marion; Pouget, Emilie; Müller-Buschbaum, Peter; Kauffmann, Brice; Pathan, Shaheen; Sagawa, Takashi; Oda, Reiko (Nano letters, 2020)
Perovskite nanocrystals (PNCs) exhibit excellent absorption and luminescent properties. Inorganic silica right (or left) handed nanohelices are used as chiral templates to induce optically active properties to CsPbBr3 PNCs grafted on their surfaces. In suspension, PNCs grafted on the nanohelices do not show any detectable chiroptical properties. In contrast, in a dried film state, they show large circular dichroism (CD) and circularly polarized luminescence (CPL) signals with dissymmetric factor up to 6 × 10–3. Grazing incidence X-ray scattering, tomography, and cryo-electron microscopy (EM) have shown closely and helically packed PNCs on the dried helices and much more loosely organized PNCs on helices in suspension. Simulations based on the coupled dipole method (CDM) demonstrate that the CD comes from the dipolar interaction between PNC assembled into a chiral structure and the CD decreases with the interparticle distance.